Empirical study on the gender gap in telework in Colombia and Ecuador - Sánchez-Gómez, Juan Sebastián; Coello Ojeda, Karín; Montoya-Noguera, Silvana; García De Cajén, Silvia (LACCEI, 2024)
This research investigates how telework impacts work-life balance for women in Colombia and Ecuador, focusing on the respect for their right to digital disconnection. Despite regulatory advances, women face challenges such as increased workload and blurred boundaries between personal and professional life. This research employs a mixed methods approach to analyze teleworking's impact on women compared to men. A questionnaire with nine constructs was used, covering behavioral changes, health risks, and boundary management. The survey, distributed via digital platforms, utilized a Likert scale and included an optional open-ended question for qualitative insights. The study surveyed 146 participants (57 men, 87 women). Men averaged 40 hours/week (SD 7.5) while women with greater variability averaged 38 hours/week (SD 12). Both genders have fixed salaries, but women often telework during emergencies and report longer workdays with increased health risks and distractions. Women also assume more household responsibilities, impacting their work-life balance. The analysis identified five boundary management styles, with significant differences in how telework affects men and women, revealing that women face more pronounced challenges. Finally, this study highlights that telework significantly impacts women, extending their workday and adding dual responsibilities from home and work. Despite shared household duties, women face greater challenges with productivity perceptions and boundary control. Interventions such as time management training and flexible policies are suggested to address these issues. This research emphasizes the importance of tailored strategies for different boundary management styles and calls for further research incorporating diverse perspectives and data sources to validate these findings